2016
DOI: 10.1111/coa.12674
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of intensity‐modulated radiotherapy as primary treatment for oropharyngeal squamous cell carcinoma – a European singleinstitution analysis

Abstract: Outcomes with IMRT are favourable, particularly in the HPV-positive patient group. This data further supports the use of a previously described prognostication model that can be used to select patients for escalation/de-escalation clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…8 "Early" late side effects until 2 years post-therapy have been described widely showing decreasing toxicities and increasing QOL up to 2 years of follow-up. 1,10,11,36,37 In contrast, a relatively small number of studies reported on VLT, probably due to the relatively low survival rates and lack of interest in the period before 2010. The emphasis of this study is put on VLT, defined as 3 to 8 years after CRT aiming at the description of incidence and evolution of very late dysphagia, xerostomia, and neck fibrosis, which are the toxicities impacting QOL most.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 "Early" late side effects until 2 years post-therapy have been described widely showing decreasing toxicities and increasing QOL up to 2 years of follow-up. 1,10,11,36,37 In contrast, a relatively small number of studies reported on VLT, probably due to the relatively low survival rates and lack of interest in the period before 2010. The emphasis of this study is put on VLT, defined as 3 to 8 years after CRT aiming at the description of incidence and evolution of very late dysphagia, xerostomia, and neck fibrosis, which are the toxicities impacting QOL most.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Long-term HNC survivors especially are significantly affected by late toxicities 6,7 ; yet the data on very late toxicity (VLT) (≥3 years after radiotherapy) remains sparse. 3 Late toxicity-generally defined as occurring >90 days after radiotherapy 8 -has been shown to decrease during the first 2 years after IMRT, 1,[9][10][11] with a more prominent improvement during the first year. 9 Nonetheless, the impact of these late toxicities on QOL remains substantial.…”
Section: Introductionmentioning
confidence: 99%
“…Our results on p16‐positive disease being significantly associated with increased nodal response even after 46 Gy radiotherapy are in line with those found in the literature. Bird et al showed that only 9% of HPV‐positive patients underwent neck dissection within 6 months of radiation completion (54–65 Gy of IMRT) because of suspected residual disease . In addition, Garden et al found that 80% of HPV‐positive patients had no neck dissection based on their response after 70 Gy of IMRT .…”
Section: Discussionmentioning
confidence: 99%
“…Bird et al showed that only 9% of HPVpositive patients underwent neck dissection within 6 months of radiation completion (54-65 Gy of IMRT) because of suspected residual disease. 24 In addition, Garden et al found that 80% of HPV-positive patients had no neck dissection based on their response after 70 Gy of IMRT. 25 They concluded that only 2% of HPV-positive OPSCC patients benefit from a neck dissection.…”
Section: Discussionmentioning
confidence: 99%
“…For stages III and IV oropharyngeal cancers, concurrent chemoradiotherapy improved DFS and OS in 2 randomized trials . As summarized in Table , the 3‐year OS of patients with oropharyngeal cancers treated with IMRT and concurrent chemotherapy ranged from 67%‐87%. Malone et al reported a 2‐year distant metastases rate of 7.5% and OS of 74.7% in patients with resectable squamous cell carcinoma of the BOT treated with multimodality therapy.…”
Section: Discussionmentioning
confidence: 99%